Dishevelled-2 regulates cocaine-induced structural plasticity and Rac1 activity in the nucleus accumbens. (26th June 2015) - Dias, Caroline; Dietz, David; Mazei-Robison, Michelle; Sun, Haosheng; Damez-Werno, Diane; Ferguson, Deveroux; Wilkinson, Matthew; Magida, Jane; Gao, Virginia; Neve, Rachael; Nestler, Eric J.
Highlights: Down-regulation of Dishevelled-2 occurs in the nucleus accumbens with cocaine. Dishevelled-2 activates Rac1 in vivo in the mature adult brain. Dishevelled-2 is important in controlling spine dynamics in response to cocaine. Abstract: Chronic cocaine exposure increases the density of dendritic spines on medium spiny neurons (MSNs), the predominant neuronal cell type of the nucleus accumbens (NAc), a key brain reward region. We recently showed that suppression of Rac1, a small GTPase, is a critical mediator of this structural plasticity, but the upstream determinants of Rac1 activity in this context remain to be elucidated. In this study we examined whether isoforms of Dishevelled, a key hub protein of multiple branches of Wnt signaling, including Rac1, are regulated in the NAc by chronic cocaine, and whether these Dishevelled isoforms control Rac1 activity in this brain region in vivo . We found that chronic cocaine administration decreased expression of Dishevelled-2, and several other Wnt signaling components, in the NAc, and that overexpression of Dishevelled-2, but not Dishevelled-1, conversely upregulated Rac1 activity and prevented the cocaine induction of dendritic spines on NAc MSNs. We posit that the cocaine-induced downregulation of Dishevelled-2 in the NAc is an upstream regulator of Rac1 activity and plays an important role in the dynamic structural plasticity of NAc MSNs seen in response to chronic cocaine exposure.